HYDROCEPHALUS ASSOCIATED WITH POLYDACTYLISM IN A LARGE WHITE YORKSHIRE PIG - GOPINATHAN, A; KARTHICKEYAN, S M K; RAMESH, J; SIVASELVAM, S N (The Indian Journal of Animal Reproduction, 2011)
A congenital abnormality of hydrocephalus associated with polydactylism was noticed in a Large White Yorkshire piglet in Pig Breeding Unit of Livestock Research Station, Kattupakkam, Tamilnadu. This female piglet was born dead with the macrocephaly and showed presence of digits instead of bifid hoofs in all four limbs and absence of dewclaw. The condition had resulted from only developmental abnormality during embryogenesis, since there was no involvement of inherited genetic cause as evident from the pedigree.